Canadian Maverick: The Life and Times of Ivan C. Rand - Kaplan, William (Published for the Osgoode Society for Canadian Legal History by University of Toronto Press, 2009)
Ivan Rand had a long, varied and remarkable career. He is best known for his Supreme Court of Canada judgments in a series of cases emanating from Quebec in the 1950s and dealing with civil rights, cases which established limits on the government’s ability to persecute unpopular religious minorities. To labour lawyers he is also an icon for his invention of the ‘Rand formula’, one of the defining features of Canadian labour law. Rand was also a member of the United Nations special committee on Palestine in 1947, the founding Dean of the University of Western Ontario law school, and three times a royal commissioner, looking into the problems of the Canadian coal industry, the misconduct of Mr. Justice Leo A. Landreville, and labour disputes in Ontario. In this thoroughly researched and fast-paced book, William Kaplan traces Rand’s life and career in all its richness and controversy – Rand as lawyer, politician, judge, dean, and royal commissioner – through many seminal events of the twentieth century in Canada. The Rand that emerges is variously inspiring, frustrating to understand, sometimes contradictory, always complex. –Publisher's description